Care consumption of people with multiple sclerosis: A multichannel sequence analysis in a population-based setting in British Columbia, Canada. (February 2022) - Roux, Jonathan; Kingwell, Elaine; Zhu, Feng; Tremlett, Helen; Leray, Emmanuelle; ,
Background: Persons with multiple sclerosis (PwMS) typically require complex multidisciplinary care, which is rarely formally assessed. Objectives: We applied multichannel sequence analysis (MCSA) to identify care consumption patterns by PwMS in British Columbia, Canada. Methods: We created two cohorts, comprising incident and prevalent MS cases, using linked clinical and administrative data. We applied MCSA to quantify and compare the care pathways of PwMS, based on all-cause hospitalizations and physician visits (divided into five specialities). Care consumption clusters were characterized using demographic and clinical features. Results: From 1048 incident and 3180 prevalent PwMS, the MCSA identified 12 and 6 distinct care consumption clusters over a median follow-up of 9.6 and 13.0 years, respectively. Large disparities between clusters were observed; the median number of annual consultations ranged from 5.6 to 21.3 for general practitioners, 1.2 to 4.6 for neurologists and 0 to 5.3 for psychiatrists in the incident cohort. Characteristics at MS symptom onset associated with the highest care consumption included high comorbidity burden and older age. There were similar disparities and associations for prevalent PwMS. Conclusion: The distinct patterns of care consumption, which were reminiscent of the heterogeneity of MS itself, may facilitate health service planning and evaluation, and provide a novel outcome measure in health research.